The Impact of Nurse-Led Innovations and Tactics During a Pandemic. Issue 3 (July 2021) - Phillips, Joan; Carr, Andrea; Guesman, Kim; Foreman-Lovell, Melissa; Levesque, Paula; Lukas, Brad; Parent, Kelly; Snyder, Dana; Grant, Susan
Abstract : The COVID-19 pandemic hit southeast Michigan hard and a rapid influx of patients forced Beaumont Health to shift rapidly into an emergency management model with a laser focus on transforming clinical care and administrative processes to meet complex patient care needs. Navigating this landscape required agility, surge planning, strong interprofessional teams, transformational leadership, nurse-led innovations, support, and transparency to manage the ever-changing environment. This article explains nursing's response and nurse-led innovations that were implemented to meet the needs of the community, patients, and staff, as well as lessons learned to ensure preparedness for any potential future surge.